Методологічні засади дослідження алармізму як культурного феномену - Малікова, Ю. (Культура народов Причерноморья, 2013)
Статтю присвячено розгляду проблемних питань методології дослідження культурних явищ
епохи Постмодерну. Подано загальний огляд традиційних наукових підходів до дефініції «алармізму» як
культурного явища епохи та окреслено проблемне поле дослідження феномену. Дослідження
культурного феномену Постмодерну набуває особливого значення в умовах відсутності орієнтирів та
інтенцій подальшого розвитку людства, оскільки пояснення сутності феномену самовідчуття страху
зможе надати змогу протистояти подальшому розповсюдженню алармістського світовідчуття,
зняти силу його ідеологічного впливу. Статья посвящена рассмотрению проблемных вопросов методологии исследования
культурных явлений эпохи Постмодерна. Представлен общий обзор традиционных научных подходов к
дефиниции «аалармизма» как культурного явления эпохи и очерчено проблемное поле исследования
феномена. Исследования культурного феномена Постмодерна приобретает особое значение в условиях
отсутствия ориентиров и интенций дальнейшего развития человечества, поскольку объяснение
сущности феномена самоощущения страха сможет предоставить возможность противостоять
дальнейшему распространению алармистского мироощущения, снять силу его идеологического влияния. The article is devoted to the investigation of problematic issues of the methodology of cultural
phenomena of Post-modernism. It provides an overview of the traditional scientific approaches to the definition
of «alarmism» as a cultural phenomenon of the era and outlined the problem field in researching of the
phenomenon.
The investigation of the cultural phenomenon of the Postmodern acquires special importance in the conditions of
absence of targets and intentions for further development of mankind as an explanation of the essence of the
phenomenon of self-feeling of fear can provide the opportunity to oppose the further spread of alarmism
ideological views, remove the power of their ideological influence.
The difficulty of understanding and investigation of alarmism is including in a dynamic phenomenon, inability of
identification of its ontological perspective, role in the culture creating processes and its influence on them. In
addition, the lack of research on this cultural phenomenon makes impossible to predict trends of further
development of alarmism in Ukraine and in the whole world.
The situation becomes complicated also because of methodological crisis faced by modern science. Throwing
away the achievements of previous eras, thinkers and philosophers of Postmodern make attempts to develop
modern methodological tools, the efficiency of which still requires verification by time. Under article an attempt of the organic connection of traditional and modern methods of investigation to such a complex and multifaceted
phenomenon as alarmism is made.